2019
DOI: 10.1080/23802359.2019.1641438
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the Ijima's Sea Snake (Emydocephalus ijimae) (Squamata, Elapidae)

Abstract: In this study, we provide the first report of the complete mitochondrial genome of Emydocephalus ijimae. The mitogenome length is 18,259 bp and includes 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and three non-coding regions. The sequence presented could be very useful for further phylogenetic and evolutionary study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
4
5
0
Order By: Relevance
“…The mitogenome contained 13 PCGs, 2 rRNA genes (12S and 16S rRNA), 22 tRNA genes, and 3 non-coding regions of two control region and an L-strand replication origin (OL). The arrangement pattern and transcribing directions of the mitogenome were identical to those of other elapid snakes (Laticauda semifasciata and Emydocephalus ijimae) previously reported (Kim et al 2018;Yi et al 2019). The phylogenetic tree for H. platurus and other related elapid snakes showed that genus Hydrophis and genus Emydocephalus formed sister groups (Figure 1) and subfamily Hydrophinae and Laticaudinae showed close relationships.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The mitogenome contained 13 PCGs, 2 rRNA genes (12S and 16S rRNA), 22 tRNA genes, and 3 non-coding regions of two control region and an L-strand replication origin (OL). The arrangement pattern and transcribing directions of the mitogenome were identical to those of other elapid snakes (Laticauda semifasciata and Emydocephalus ijimae) previously reported (Kim et al 2018;Yi et al 2019). The phylogenetic tree for H. platurus and other related elapid snakes showed that genus Hydrophis and genus Emydocephalus formed sister groups (Figure 1) and subfamily Hydrophinae and Laticaudinae showed close relationships.…”
supporting
confidence: 77%
“…Yellow-bellied sea snakes (Hydrophis platrus) have the largest and broadest distribution range of all species in the order Squamata (Brischoux et al 2016). Although their distribution is broad, only the complete mitochondrial DNA of three sea kraits (Laticaudinae) and one sea snake are known and there are no published studies on H. platurus (Kim et al 2018;Yi et al 2019). The H. platurus specimen was collected from Seongsan-eup, Seogwipo-si, Jeju-do, Republic of Korea (33 11 0 N and 127 33 0 E) on 26 June 2017.…”
mentioning
confidence: 99%
“…Three clades (Bungarus, Micrurus and Naja) represented terrestrial elapids and Laticauda exemplified aquatic elapids. Among terrestrial elapids Bungarus is a sister group of Micrurus with Naja as an outgroup, all with highly supported nodes, and patterns identical to those reported previously (Kim et al 2018;Yi et al 2019). The complete mitochondrial genome sequence of Micrurus surinamensis has been deposited in GenBank (accession number: MN587874).…”
supporting
confidence: 57%
“… 2018 ; Yi et al. 2019 ). The complete mitochondrial genome sequence of Micrurus surinamensis has been deposited in GenBank (accession number: MN587874).…”
mentioning
confidence: 99%
“…Hydrophis melanocephalus, a rarely studied slender-necked sea snake, has been often confused with other snakes, such as H. coggeri in the Australian region (Kharin 1984), Emydocephalus ijimae in Japan (Yi et al 2019), and H. platurus and Laticauda semifasciata in Korea (Kim et al 2018;Kim et al 2020). Hydrophis melanocephalus is known to be distributed in Vietnam, China, Taiwan, Japan, and Philippines (David and Ineich 1999;Kharin and Czeblukov 2006).…”
mentioning
confidence: 99%